Utilization of Instagram through the @jktinfo Account as a Means of Fulfilling Information for the People of Jakarta (Open Society Conference, 2023)
(Instagram is a social media used massively in the era of society 5.0. Because of its massive use, Instagram is now not only a social media but also the primary source of information searches. The Instagram account @jktinfo has 3.3 million followers, providing the latest information about Jakarta. The information provided by @jktinfo comes from various sources, both provided by account managers and their followers. This research discusses how Instagram is used as a medium to fulfil the information needs of the Jakarta people. This research is conducted by looking at followers' perceptions after viewing the @jktinfo account. The method used in this research is descriptive qualitative. Data collection techniques in this research are interviews, observation and documentation carried out to followers of the @jktinfo account. The theory used is Information Richness Theory. The results of this study show that followers of the @jktinfo account use Instagram as the primary source of information. In addition, some of them use the @jktinfo account to fulfil information without looking at the validity of the information.